2015
DOI: 10.1080/14786419.2014.1000894
|View full text |Cite
|
Sign up to set email alerts
|

Fungistatic activity ofZanthoxylum rhoifoliumLam. bark extracts against fungal plant pathogens and investigation on mechanism of action inBotrytis cinerea

Abstract: Plant-derived compounds are emerging as an alternative choice to synthetic fungicides. Chloroform-methanol extract, obtained from the bark of Zanthoxylum rhoifolium, a member of Rutaceae, showed a fungistatic effect on Botrytis cinerea, Sclerotinia sclerotiorum, Alternaria alternata, Colletotrichum gloeosporioides and Clonostachys rosea, when added to the growth medium at different concentrations. A fraction obtained by gel separation and containing the alkaloid O-Methylcapaurine showed significant fungistatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…According to Carotenuto et al (2015) with modifications, the evaluation of inhibition of mycelial growth of the phytopathogen was carried out by adding to the surface of the 9 cm diameter Petri dish containing approximately 20 ml of BDA culture medium already solidified, 100 μL of the extracts of the endophytic fungi. The extracts were diluted in Tween 80 and water.…”
Section: Selection According To Fungitoxicity Against C Lunatamentioning
confidence: 99%
“…According to Carotenuto et al (2015) with modifications, the evaluation of inhibition of mycelial growth of the phytopathogen was carried out by adding to the surface of the 9 cm diameter Petri dish containing approximately 20 ml of BDA culture medium already solidified, 100 μL of the extracts of the endophytic fungi. The extracts were diluted in Tween 80 and water.…”
Section: Selection According To Fungitoxicity Against C Lunatamentioning
confidence: 99%
“…Costa et al (2008) identified antibacterial and larvicidal effects in the essential oil extracted from the fruit. Z. rhoifolium bark extract showed analgesic activity, popularly mentioned for toothache and earache, as well as fungicidal activity (Pereira, et al, 2010;Carotenuto, et al, 2015). The study by Jullian et al (2006) was able to prove the antimalarial potential of the shell.…”
Section: Introductionmentioning
confidence: 86%
“…The bark extract has also demonstrated analgesic activity, popularly mentioned for toothache and earache, as well as fungicidal activity (Pereira, et al, 2010;Carotenuto, et al, 2015). Furthermore, Jullian et al (2006) were able to prove the antimalarial potential of the shell.…”
Section: Introductionmentioning
confidence: 94%
“…The genus Zanthoxylum (Rutaceae) includes about 250 species distributed throughout the world; among these, the Zanthoxylum rhoifolium species, native to South America, has long been used in traditional Brazilian medicine to treat various health problems [34] and in French Guiana as antimalarial treatment [35]. These plants are known to be a rich source of natural alkaloids and lignans, which are extracted from the bark [36]. Some of these alkaloids, including benzofenantridine and fluoroquinolones, exhibit a variety of biological activities: anticancer [37], antimicrobial [38], anti-inflammatory [39] and antifungal [40,41] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these alkaloids, including benzofenantridine and fluoroquinolones, exhibit a variety of biological activities: anticancer [37], antimicrobial [38], anti-inflammatory [39] and antifungal [40,41] activities. Moreover, recently, Zanthoxylum rhoifolium extracts showed a fungistatic effect on different fungal plant pathogens, such as, Botrytis cinerea, Sclerotinia sclerotiorum, Alternaria alternata, Colletotrichum gloeosporioides and Clonostachys rosea [36].…”
Section: Introductionmentioning
confidence: 99%